Bridging the Dualist Pairs: An Ecofeminist Reading of Caryl Churchill’s Fairy Tale Inter-text in The Skriker - Şahin Gülter, Işıl (Istanbul University Press, 2025)
Drawing mainly upon the critique of the dualisms of the ecofeminist literary theory, this article establishes connections between the dramatic structure of Caryl Churchill’s The Skriker (1994), populated with anti-rational forces like fairies, spirits, goblins, and monsters, and the theory of ecofeminism. Thus, this article aims to reveal complementary ways of thinking about questions of dualism that are applicable to theatre studies. Accordingly, this article brings an anti-dualist feminist perspective to The Skriker, arguing that the play employs its fairy elements to avoid boundaries between dualist pairs so that all categories can be reconceptualized in ways that challenge polarisation. In this sense, the article indicates that the fairy character Skriker’s swift crosses between the dualist pairs of male/female, human/nonhuman, and conscious/unconscious realms, and the idiosyncratic language relate to the interconnectedness between those dualist pairs, highlighting the possibilities through which they may be reconsidered in an interactive and complementary way. © 2025. Şahin Gülter, I.
Keywords: Caryl Churchill; Dualism; Ecofeminist Drama; Fairy Tale; The Skriker